Towards the chemical standardisation of Epilobium hirsutum leaves - Uminska, Kateryna; Ivanauskas, Liudas; Jarukas, Laurynas; Georgiyants, Victoriya; Mykhailenko, Olha (ScienceRise: Pharmaceutical Science, 2026)
Epilobium hirsutum L. is widely used in traditional European medicine to treat urological and inflammatory conditions. Despite its widespread use, no pharmacopoeial monographs on its plant material have been published to date. The aim of this study was to establish physicochemical parameters and identify marker phenolic compounds for the standardisation of plant leaves. Method. Seven E. hirsutum leaf samples collected in Ukraine, Lithuania, and Poland for analysis. The following parameters were analysed: loss on drying, total ash, and acid-insoluble ash content according to the State Pharmacopoeia of Ukraine. The qualitative composition was analysed using high-performance thin-layer chromatography (HPTLC), and the quantitative analysis of total phenolic compounds, flavonoids, and specific marker compounds was performed using UV spectrophotometry and HPLC-DAD. Results. As a result, it was established that the content of foreign impurities did not exceed 2% in the analysed samples, the drying loss was 6.4–8.1%, and the total ash was 4.0–5.7%. The HPTLC method was used to determine gallic acid, isoquercitrin, avicularin, guijaverin and hyperoside as key compounds for the plant quality control. Total phenolics ranged between 0.78 and 1.52 mg GAE/g dw, while total flavonoid content was 1.9–5.5 mg HE/g dw. The HPLC method showed that the dominant polyphenolics is oenothein B (39.9–65.7 mg/g), followed by oenothein A, gallic, chlorogenic, and ellagic acids, hyperoside, isoquercitrin, and quercetin. The present components can be proposed for the development of raw material standardisation parameters. Conclusion. The obtained data confirm that E. hirsutum leaves meet requirements of the State Pharmacopeia of Ukraine and European Pharmacopoeia and can serve as the basis for developing a monograph. Oenothein B, hyperoside, and gallic acid can be proposed as identification markers; in addition, the total phenolic content can be assessed